Informational Behaviors and Innovation in SMEs: An Application to the Cameroonian agri-Food Sector (Global Journal of Management and Business Research, 2022)
Nowadays, for companies that want to experience strong growth, information systems have become essential. But it is the informational behaviours of individuals who form these systems that make them effective and efficient within a company. And thus, these behaviors can make companies innovative over a long period. The information system of a company is an effective means to improve performance and thus increase competitiveness (Thomas and Muller, 1996). This research aims to evaluate the contribution of managers informational behaviours to the innovation of SMEs in the agri-food sector. To carry out this study, we conducted an exploratory qualitative approach based on case studies to better understand this problem, and then we carried out a review of the literature on the concepts of informational behaviour and innovation. However, our research shows that the more effective and efficient informational behaviours of managers, the more they contribute to the creation of a product innovation.
Keywords: informational behaviour; product innovation; agri-food SMEs; information